Estimating state and sub‐state economic effects of a carbon dioxide tax policy: An application of a new multi‐region energy‐economy econometric model1. Issue 3 (August 2015) - Warren, David C.; Wendling, Zachary A.; Bower‐Bir, Jacob; Fields, Henry; Richards, Kenneth R.; Carley, Sanya; Rubin, Barry M.
Abstract This paper discusses an innovative econometric approach for modelling how national or state‐level energy policies can affect state and sub‐state economic outcomes using the new Indiana scalable energy‐economy model (IN‐SEEM). This model – which can be modified and scaled to investigate other states and sub‐state regions – is used to analyse the economic effects of a carbon dioxide (CO2) tax on the state of Indiana and two of its most populous regions. Results of this analysis offer a proof‐of‐concept for an econometric approach that allows for sub‐state analysis of energy policies. Further, the policy analysis finds that without a mechanism for recycling CO2 tax revenues back into the economy, a CO2 tax of between $15 and $45 per ton will have a significant negative effect on the state economy and the two regions examined. While we find the tax to be an effective means of reducing energy consumption and thus CO2 emissions, total employment and gross state product per capita are forecast to decline 4.0 and 3.2 per cent, respectively, for the state given a $15 per ton CO2 tax in the year 2025.